Nanomaterials for diagnostic, treatment and prevention of COVID-19 - Adhikari, Subash; Adhikari, Usha; Mishra, Akash; Guragain, Bhim Sagar (Applied Science and Technology Annals, 2020)
The global outbreak of coronavirus disease (COVID-19) has set an alarming message for the research and discovery of new and advance technology. This is possible by either combining the convectional technology with modern discoveries or initiating new avenues of research using nanotechnology. The vast library of nanomaterials and its integration into modern technology can offer various possibilities for discovery of nanomedicines, nano-biosensors, nanocompounds for controlling the sever acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and other similar virus outbreaks. Here we review the ongoing approaches utilized in detection, treatment and prevention of SARS-CoV-2 and describe their advantages and drawbacks. Additionally, we provide the new and innovative technology that are currently being researched or commercialized with the aid of nanomaterials and nanotechnology for disease identification, treatment and control. We further suggest new research area based on natural product research that can provide new opportunities for jobs and economic movements during the post-COVID-19 pandemic.